Utility of pyrosequencing for rapid detection of tubercular meningitis (TBM) and associated susceptibility directly from CSF specimens. (July 2018) - Ajbani, Kanchan; Kazi, Mubin; Naik, Swapna; Soman, Rajeev; Shetty, Anjali; Rodrigues, Camilla
Abstract: Tubercular meningitis (TBM) is a serious form of tuberculosis (TB). The diagnosis of TBM & susceptibility/resistance is difficult as TB MGIT culture lacks sensitivity & timeliness. Timely and accurate diagnosis of the TBM is the need of the hour for initiation of appropriate therapy. We have exploited pyrosequencing to detect TB and associated Multi/extensively drug resistant (MDR/ XDR-TB) directly from Cerebrospinal Fluid (CSF) specimens.